Osteossarcoma de patela em cão. Relato de caso - Selmi, A. L.; Nishiya, A. T.; Moreira, M. A. B.; Moura, C. A.; Provasi, A.; Eimantas, G. C.; Coelho, H. C. C.; Guerra, J. L. (Brazilian Journal of Veterinary Research and Animal Science, 2003)
O artigo não apresenta resumo.